Analysis of the Effect of Firm-Generated Content (FGC) and User-Generated Content (UGC) on Brand Trust and Perceived Value mediated by Social Media Brand Engagement (SMBE): Empirical Study on Residential Property in Indonesia - Matra, Velisia Visiana; Aruan, Daniel Tumpal Hamonangan (SAFE-Network, 2025)
This study aims to explore the impact of User Generated Content (UGC) and Firm Generated Content (FGC) on brand engagement in social media, referred to as Social Media Brand Engagement (SMBE), as well as their effects on brand trust, consumer satisfaction, and perceived value. The research employs a quantitative approach, collecting data through surveys involving 369 respondents sampled from followers of residential property brand accounts and residential property influencer accounts in Indonesia. The findings indicate that both UGC and FGC have a significant positive influence on brand trust and perceived value, with SMBE serving as a mediator in these relationships. However, the results also reveal that Social Media Influencer Endorsement does significantly moderate the relationship between FGC and SMBE, and Self-image Congruence does significantly moderate the relationship between UGC and SMBE. The results of this study provide practical guidance for companies in the property sector to leverage UGC and FGC in their marketing strategies. By understanding the importance of brand engagement in social media, companies can enhance their relationships with consumers and achieve better outcomes in digital marketing.